Legal Protection for the Partnership Agreement Parties - Widaningsih, Widaningsih; Suhariningsih, Suhariningsih; Sihabuddin, Sihabuddin; Santoso, Budi (Al-Risalah, 2022)
Preparing the partnership agreement must comply with the rules for the parties to get guarantees and legal protection. The rules must meet the preliminary requirements, such as understanding the transaction object and background, compiling its outline, recognizing the partners, and formulating the agreement principles. The partnership agreement must also have a signature, as well as rights and obligations. This normative study aimed to analyze the partnership agreement rules as legal protection. The results showed that the partnership agreement rules contain all the parties need as legal certainty and protection.